Analisis Kesulitan Pemahaman Konseptual Siswa dalam Materi Aljabar Berdasarkan Teori APOS - Maulina, Sri; Muchtadi, Muchtadi; Hartono, Hartono (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to find out the difficulty of students' conceptual understanding in algebra material based on APOS theory. The research approach is qualitative with the type of research is a case study. The sample selection technique used is purposive sampling. The source of data in this study is 31 students in grade VII F SMP Negeri 4 Singkawang for the 2023/2024 school year. Furthermore, 6 more students were taken as subjects to be interviewed. Data collection techniques use tests, interviews and documentation. The data analysis techniques are: 1) Data Collection, 2) Data Reduction, 3) Data Display, and 4) Conclusion Drawing/Verification. The results of the study show that: 1) The difficulty of mathematical conceptual understanding of students with APOS theory of the high category is the lack of understanding of students' concepts in Algebra material, lack of accuracy in reading problems and lack of understanding of the meaning of the problem; 2) The difficulty of mathematical conceptual understanding of students with APOS theory in the medium category is lack of understanding of the concept of similar terms in Algebra, confusion about how to explain the reason and mathematical model, lack of mastery of the concept of calculation operations on integers, lack of mastery of distributive concepts applied to Algebraic forms; 3) The difficulty of mathematical conceptual understanding of students with APOS theory in the low category is the difficulty in applying the basic concepts of Algebra